The Impact of the Built Environment on Resident Well-Being: The Mediating Role of Multidimensional Life Satisfaction - Tunan Deng; Chun-Ming Hsieh; Anan Guan; Xueying Wu (Buildings, 2025)
Well-being is an important goal pursued by humans, and the living environment has a profound impact on various aspects of human health. The objective of this study is to explore the mechanism by which the built environment affects the well-being of residents, specifically how multiple, distinct domains of life satisfaction mediate the effects of diverse built environment features on well-being—a nuanced pathway not yet comprehensively examined. Based on questionnaire data collected from 22 statistical districts in Macau, with a sample size of 1313 individuals, a multilevel linear regression model and mediation analysis were applied (model R2 ≈ 47%). When leisure satisfaction is used as a mediator variable alone, the explanatory power of the original model increases the most (from 7.6% to 32%). Complete Mediation via Specific Domains: Health satisfaction fully mediated the effects of intersection density (p < 0.05) and bus stop accessibility (p < 0.05). All four satisfaction domains collectively fully mediated income diversity (Shannon index, p < 0.01). The 14 built environment metrics (5 socioeconomic, 9 morphological) exhibited differential mediation mechanisms: while transportation-related metrics (intersection density, bus stops) primarily operated through health/social satisfaction, diversity indices (income, education, land use) and unemployment rate engaged all satisfaction domains. Some variables showed partial mediation through various satisfaction pathways (p < 0.01–0.05). These findings underscore the necessity of considering multidimensional life satisfaction as critical pathways in urban well-being research and policy.